2020
DOI: 10.3892/br.2020.1343
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum levels of anti‑cyclic citrullinated peptide antibodies in patients with psoriatic arthritis: A cross‑sectional study in a Brazilian cohort

Abstract: Presence of the anti-cyclic citrullinated peptide (CCP) antibody is considered a hallmark of rheumatoid arthritis, and may be found in patients with other rheumatic diseases, including psoriatic arthritis (PsA). The aim of the present study was to determine whether the anti-CCP antibody was present in patients with psoriasis with and without arthritis. and to determine whether its presence was associated with clinical, serological and treatment data in patients with PsA. The present study was a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The seronegative of RF and ACPA are regarded as one of clinical features of PsA to differentiate with RA, which were also included in CASPAR criteria as one item (26). However, the seropositivity of RF/ACPA were found in 5-20% of PsA patients (27)(28)(29). Therefore, the seropositivity of RF/ACPA does not exclude a diagnosis of PsA, although nearly thirty percent of rheumatologists have a wrong understanding of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The seronegative of RF and ACPA are regarded as one of clinical features of PsA to differentiate with RA, which were also included in CASPAR criteria as one item (26). However, the seropositivity of RF/ACPA were found in 5-20% of PsA patients (27)(28)(29). Therefore, the seropositivity of RF/ACPA does not exclude a diagnosis of PsA, although nearly thirty percent of rheumatologists have a wrong understanding of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lack of RF is suggestive of PsA [ 18 ], it can be found in up to 20% of PsA patients [ 19 ]. Moreover, ACPA antibodies are found in 20.9% of PsA patients according to Gruber et al [ 20 ]. This study also found that, in the group of patients with PsA, those who were ACPA positive were more likely to present the polyarticular form of arthritis.…”
Section: Introductionmentioning
confidence: 99%